Social Enterprise Emergence from Social Movement Activism: The Fairphone Case. (26th April 2016) - Akemu, Ona; Whiteman, Gail; Kennedy, Steve
Abstract: Effectuation theory invests agency – intention and purposeful enactment – for new venture creation in the entrepreneurial actor(s). Based on the results of a 15‐month in‐depth longitudinal case study of Amsterdam‐based social enterprise Fairphone, we argue that effectual entrepreneurial agency is co‐constituted by distributed agency, the proactive conferral of material resources and legitimacy to an eventual entrepreneur by heterogeneous actors external to the new venture. We show how in the context of social movement activism, an effectual network pre‐committed resources to an inchoate social enterprise to produce a material artefact because it embodied the moral values of network members. We develop a model of social enterprise emergence based on these findings. We theorize the role of material artefacts in effectuation theory and suggest that, in the case, the artefact served as a boundary object, present in multiple social words and triggering commitment from actors not governed by hierarchical arrangements.